Integrating blockchain with lattice-based cryptography for privacy-preserving and quantum-secure smart grid communications - Habib, Umair; Bano, Mahwish; Iqbal, Jawaid; Hajjej, Fahima; Ullah, Insaf (Frontiers in Physics, 2026)
The Smart Grid (SG) is an upgraded electrical system integrated with Information and Communication Technology (ICT) to provide two-way data exchange between power consumers and manufacturers. This innovation facilitates smooth digital connectivity between smart devices like Smart Appliances (SAs), Smart Meters (SMs), and the Service Provider (SP), enabling remote data management to achieve enhanced energy distribution. However, using insecure wireless communications channels poses serious security threats, such as replay, impersonation, man-in-the-middle, and physical capture attacks. Numerous cryptographic algorithms, including RSA, Bilinear Pairing, Data Encryption Standard (DES), and Advanced Encryption Standard (AES), are used in existing studies to address the problem of information breakout. Furthermore, because the parameters and key space are so large, these methods suffer from higher computing costs and communication overhead. To resolve this issue, we have proposed a lattice-based privacy-preserving framework for the SG network that can withstand quantum attacks. Moreover, because quantum computers cannot solve the lattice-based hard problems, the lattice-based signcryption scheme is developed to resist quantum attacks. We have also integrated blockchain technology with the proposed scheme to make the data tamper-resistant and secure against adversary attacks. The proposed protocol is intended to offer data confidentiality, data integrity, and unforgeability. The proposed protocol also withstands several known attacks, such as Man-in-the-Middle (MITM), replay, known session key, insider, and post-quantum attacks. We have simulated our scheme using the AVISPA simulation program, which proves the efficiency and effectiveness of our proposed scheme in meeting the required security properties.